Protein supplements for feedlot rations compared - Shiawoya, E.L.; Harbers, L.H.; Bolsen, K.K.; Riley, Jack G.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Protein supplements composed of either soybean meal, a combination of soybean meal and urea, or milo Starea improved gain 5% and feed efficiency 4% over supplements of either urea or wheat Starea (P<.25). Cost of gain favored the nonprotein nitrogen compounds; thus, choice of supplement was related to relative cost of supplements.
Keywords: Beef; Protein; Feedlot rations